Exploring Structure and Function of Redox Intermediates in [NiFe]‐Hydrogenases by an Advanced Experimental Approach for Solvated, Lyophilized and Crystallized Metalloenzymes. Issue 29 (5th May 2021) - Lorent, Christian; Pelmenschikov, Vladimir; Frielingsdorf, Stefan; Schoknecht, Janna; Caserta, Giorgio; Yoda, Yoshitaka; Wang, Hongxin; Tamasaku, Kenji; Lenz, Oliver; Cramer, Stephen P.; Horch, Marius; Lauterbach, Lars; et al.
Abstract: To study metalloenzymes in detail, we developed a new experimental setup allowing the controlled preparation of catalytic intermediates for characterization by various spectroscopic techniques. The in situ monitoring of redox transitions by infrared spectroscopy in enzyme lyophilizate, crystals, and solution during gas exchange in a wide temperature range can be accomplished as well. Two O2 ‐tolerant [NiFe]‐hydrogenases were investigated as model systems. First, we utilized our platform to prepare highly concentrated hydrogenase lyophilizate in a paramagnetic state harboring a bridging hydride. This procedure proved beneficial for 57 Fe nuclear resonance vibrational spectroscopy and revealed, in combination with density functional theory calculations, the vibrational fingerprint of this catalytic intermediate. The same in situ IR setup, combined with resonance Raman spectroscopy, provided detailed insights into the redox chemistry of enzyme crystals, underlining the general necessity to complement X‐ray crystallographic data with spectroscopic analyses. Abstract : A multifunctional setup for in situ spectroscopy on gas‐processing metalloenzymes enables the controlled preparation of redox states in various sample forms. This setup allowed the first NRVS characterization of the Nia −C state of [NiFe]‐hydrogenases, provided new insights into the reductive activation of these enzymes, and revealed a so‐far unknown redox state of the oxygen‐tolerant membrane‐bound hydrogenase from R. eutropha .